Fractional Erbium-YAG Laser and Platelet-Rich Plasma as Single or Combined Treatment for Atrophic Acne Scars: A Randomized Clinical Trial - Moustafa A. El-Taieb; Hassan M. Ibrahim; Eisa M. Hegazy; Ahmed K. Ibrahim; Aya M. Gamal; Essam A. Nada (Adis, Springer Healthcare, 2019)
Abstract Introduction Acne scarring is a common undesirable complication of acne vulgaris. Fractional erbium-yttrium aluminum garnet (YAG) 2940 nm laser and platelet-rich plasma have been used in treating acne scars with variable outcomes. The objective of this study is to assess the efficacy of fractional erbium-YAG 2940 nm laser and platelet-rich plasma as a single line of treatment in comparison with combined treatment in atrophic postacne scars. Methods Seventy-five patients were included in this trial and randomized into three equal groups (25 each). Group A was subjected to six sessions of erbium-YAG laser for 6 months, group B was treated with 12 sessions of platelet-rich plasma over the same period, and group C was subjected to six sessions of erbium-YAG laser plus 12 sessions of platelet-rich plasma over the same period. Each subject was evaluated by acne scar grading, photography, and subjective evaluation. Results Both treatment modalities showed improvement of acne scars, but the improvement with combined treatment was better than that with erbium-YAG laser or platelet-rich plasma alone regarding scar grade improvement (P = 0.007 and 0.001), clinical improvement (P = 0.001 and 0.001), and patient satisfaction (P = 0.005 and 0.001), respectively. Conclusions The combination of platelet-rich plasma plus erbium-YAG laser is superior to either treatment alone for acne scars, with trivial side effects for all treatment modalities. Trial Registration ClinicalTrials.gov identifier; NCT03933033.